Intersubband optical transitions in one dimensional quantum wire structures - Sa'ar, A.; Givant, A.; Calderon, S.; Ben-Shalom, O.; Kapon, E.; Gustafsson, A.; Oberli, D.; Caneau, C. (Superlattices and microstructures, 1996)
One dimensional (1D) quantum wire structures are emerging as the new generation of semiconductor nanostructures offering exciting physical properties which have significant potential for novel device applications. These structures have been the subject of intensive investigation recently including extensive theoretical and experimental studies of their interband optical properties. In this work we present the results of our study of the intersubband optical transitions in 1D semiconductor quantum wires. The crescent shaped quantum wire structures used for this research were grown on non-planar GaAs substrates. The intersubband transition energy spectra, the selection rules, and the two dimensional envelope wavefunctions were theoretically investigated by using our new LENS (local envelope states) expansion. We present recent experimental results on modulation doped V-groove quantum wires, including PL, PLE, TEM, CL, and infrared polarization resolved spectroscopy. We have observed a very unusual absorption lineshape at the far-infrared wavelengths that we assigned to phonon assisted Fano resonance in a modulation doped quantum wire structure.